2013
DOI: 10.1254/jphs.13094fp
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Millettia macrophylla (Fabaceae) Extracts on Estrogen Target Organs of Female Wistar Rat

Abstract: Abstract. The present study aims to determine the estrogenicity of Millettia macrophylla, a Cameroonian medicinal plant, in ovariectomized rats and to investigate the underlying mechanisms, in order to justify scientifically its traditional use. To accomplish this objective, we used dichloromethane (DCM) and methanol (MeOH) extracts of the stem bark of M. macrophylla. In the cell culture based assay, the MeOH extract significantly transactivated estrogen receptor a (ERa) and estrogen receptor b (ERb); in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 35 publications
8
26
0
Order By: Relevance
“…For these authors, fourteen days of estrogens decline after ovariectomy induced an atrophy of the vaginal epithelium, the reduction of the uterine wet weight, uterine epithelium height and total protein levels in this uterine. The results are also in agreement with those of Bocchinfuso et al [33] and Zingue et al [34] which have shown that in the mammary glands ovariectomy induces a stop of the production of eosinophilic secretion in the lumen of alveoli. These results suggest that estrogen decline was induced fourteen days after ovariectomy.…”
supporting
confidence: 92%
“…For these authors, fourteen days of estrogens decline after ovariectomy induced an atrophy of the vaginal epithelium, the reduction of the uterine wet weight, uterine epithelium height and total protein levels in this uterine. The results are also in agreement with those of Bocchinfuso et al [33] and Zingue et al [34] which have shown that in the mammary glands ovariectomy induces a stop of the production of eosinophilic secretion in the lumen of alveoli. These results suggest that estrogen decline was induced fourteen days after ovariectomy.…”
supporting
confidence: 92%
“…The Human Embryonic Kidney 293 T cell line (HEK293T) was transiently transfected with adequate plasmids using Lipofectamine Reagent as previously described by Zingue et al [18]. They were then treated with different concentrations [10 −9 to 10 −5 M for stigmastenone (3) and 10 −5 to 10 −1 μg/mL for phenolic fraction] for 24 h. Cells treated with E2 (10 nM) alone served as positive control.…”
Section: Methodsmentioning
confidence: 99%
“…This decrease in intromission could be associated with erectile dysfunction, as described by Yakubu and Afolayan [47], suggesting that the MeOH extract of M. macrophylla alters erectile function. This alteration could be due to the presence of isoflavonoids in this extract [35]. Isoflavonoids modulate dopaminergic transmission in the brain, thereby influencing sexual behavior [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Our botanical sample was identified and authenticated by Mr. Victor Nana, botanist at the National Herbarium of Cameroon (HNC) in Yaounde (Voucher specimen number 49654/HNC). The methanol extract (MeOH) and the dichloromethane extract (DCM) used in this study were extracted as described previously by Zingue et al [35]. The doses of 100, 200, and 300 mg/kg body weight (BW) used in this study were effective doses obtained in our previous work and derived from the traditional doses [35].…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation